The Concept Of Good Corporate Governance In A Limited Liability Company's Account Receivable Policy For Potentially Insolvent Companies - Ilham, Rico Nur; Sinta, Irada; Sinurat, Mangasi; Khaddafi, Muammar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The application of Good Corporate Governance (GCG) concept in receivable policies is crucial, especially for companies facing potential bankruptcy. This research aims to explore how the GCG concept can be implemented in the receivable policies of limited liability companies facing bankruptcy risks. The introduction explains the urgency of GCG in managing receivables and the potential negative impact if not managed properly. The research of tisn method employs a qualitative approach with a case study of several companies facing bankruptcy risks. Data were obtained through interviews with company management, document analysis, and relevant literature review on GCG and receivable policies. The main issues identified include the lack of transparency in receivable policies, ineffective credit risk management, and non-compliance with financial regulations. The research findings indicate that companies implementing the GCG concept in receivable policies tend to have better financial performance and are better able to manage bankruptcy risks. In conclusion, the GCG concept can serve as an effective framework in managing receivable policies of limited liability companies facing potential bankruptcy. By considering transparency, risk management, and compliance with regulations, companies can minimize bankruptcy risks and ensure long-term business sustainability